2018
DOI: 10.1186/s12879-018-3082-0
|View full text |Cite
|
Sign up to set email alerts
|

MDR1 overexpression combined with ERG11 mutations induce high-level fluconazole resistance in Candida tropicalis clinical isolates

Abstract: BackgroundMarked increases in fluconazole resistance in Candida tropicalis have been recently reported. In this study, the molecular mechanisms behind fluconazole resistance were investigated.MethodsTwenty-two C. tropicalis clinical isolates, including 12 fluconazole-resistant isolates and 10 fluconazole-susceptible isolates, were collected from a tertiary care teaching hospital in Beijing between 2013 and 2017. Antifungal susceptibility testing, multilocus sequence typing, ERG11 amplification and sequencing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 25 publications
6
43
0
Order By: Relevance
“…The increased resistance rate of C. tropicalis to azole antifungal drugs might be related to the easy application of such drugs and the relatively mild adverse reactions [18]. In the clinic, a large number of patients with severe fungal infections and long-term application of these drugs were subjected to prophylactic treatments, which would lead to drug resistance [19]. Moreover, in this study, the ERG11 and UPC2 genes of 50 strains of C. tropicalis were assessed, and our results showed that the relative expression level of the ERG11 gene in the drug-resistant group was higher than it was in the sensitive group, which is in line with the ndings from Jiang et al [20] regarding the high expression of ERG11 in uconazole-resistant C. tropicalis.…”
Section: Discussionmentioning
confidence: 99%
“…The increased resistance rate of C. tropicalis to azole antifungal drugs might be related to the easy application of such drugs and the relatively mild adverse reactions [18]. In the clinic, a large number of patients with severe fungal infections and long-term application of these drugs were subjected to prophylactic treatments, which would lead to drug resistance [19]. Moreover, in this study, the ERG11 and UPC2 genes of 50 strains of C. tropicalis were assessed, and our results showed that the relative expression level of the ERG11 gene in the drug-resistant group was higher than it was in the sensitive group, which is in line with the ndings from Jiang et al [20] regarding the high expression of ERG11 in uconazole-resistant C. tropicalis.…”
Section: Discussionmentioning
confidence: 99%
“…As for other NAC species, MDR was reported in some studies and, strikingly, almost 1% of the Indian C. tropicalis blood isolates are resistant to the three major classes of antifungals [138]. Unlike C. parapsilosis, it appears that ERG11 overexpression is a more prominent FLZR mechanism than efflux pump activity in C. tropicalis [151][152][153][154], and MDR1 overexpression [152,155,156] is more prevalent than CDR1 overexpression [152,156]. Surprisingly, FLZR C. tropicalis isolates lacking any accountable mutation in ERG11 and not overexpressing efflux pumps were also identified, suggesting the involvement of other, unknown, mechanisms [156].…”
Section: Candida Tropicalismentioning
confidence: 91%
“…The increased resistance rate of Candida tropicalis to azoles might be related to the easy application of such drugs and the relatively mild adverse reactions [17]. In clinic, a large number of patients with severe fungal infections and long-term application of these drugs were subjected to the prophylactic treatments, which would lead to the drug resistance [18]. Moreover, in this study, the ERG11 and UPC2 genes of 50 strains of Candida tropicalis were detected, and our results showed that the relative expression level of ERG11 gene in the drug-resistant group was significantly higher than the sensitive group, in line with the findings from Jiang et al [19] concerning the high expression of ERG11 in fluconazole-resistant fungi.…”
Section: Discussionmentioning
confidence: 99%